Factors Affecting the Children in Conflict with The Law in Soccsksargen, Philippines - ñ on Rendaje, Ma. Odeza Ani; Rendaje Jr., Ludivico Villa; Cariño, Cristine Fajanibo; Pua, Ronnie Rendon; Salas Jr., Apolinario Caballes; Villa, Elizabeth Buena (Future Science / FSH-PH Publications, 2024)
T he study aimed to evaluate the factors influencing children involved in legal conflicts in the SOCCSKSARGEN region. The local government of SOCCSKSARGEN is adopting various strategies to address the problem of Children in Conflict with the Law (CICLs) in South Cotabato, Cotabato Province, Sultan Kudarat, Sarangani, and General Santos City. One of the procedures entails establishing the Bahay Pag-asa, a rehabilitation center for children in conflict with the law (CICLs) and at-risk youth. The study participants were of juveniles involved in criminal activities residing at St. Marcelline in General Santos City. These children were placed in the institution to redirect their focus and provide them with a safe haven while their case is being decided. This study employed a quantitative-descriptive design. This study employed the survey approach to gather information about the demographic profile and factors influencing youth involved in criminal activities, such as family relationships, peer influence, and external environmental factors. The conclusions drawn are based on the collected data. 1. Children in Conflict with the Law were of various ages, ranging from 9 to 21 years old, at the time of committing the crime. 2. The majority of these children were influenced by their family dynamics, which led them to engage in criminal activities. 3. The objective is to facilitate the reintegration of children in conflict with the law into society after their case is resolved. The aforementioned programs and services encompassed residential care services, including caring, healing, life skills intervention program, and teaching, as well as a juvenile justice program, technical skills program, and independent living program. This study examines the impact of several influences in the community on youngsters involved in criminal activities. Additionally, it might be inferred that the societal standards in their previous place of residence had ingrained a certain psychological impact on them, causing their sense of wrongdoing to be hindered.